Functional and anatomical imaging in pediatric oncology: which is best for which tumors - Voss, Stephan D. (Pediatric radiology, 2019)
Functional imaging techniques are playing an increasingly important role in the management of pediatric cancer. Technological advances have pushed the development of hybrid imaging techniques, including positron emission tomography (PET)/CT, PET/MR and single-photon emission computed tomography (SPECT)/CT. Together with an increasing need to identify surrogate biomarkers for response to novel therapies, the use of functional imaging techniques, which had been reserved primarily for lymphoma patients, is now being recognized as standard of care for the management of many other pediatric solid tumors. The purpose of this review is to summarize recent data describing the use of functional and metabolic imaging strategies for the staging and response assessment of common pediatric solid tumors, and to offer some guidance as to which techniques are most appropriate for which tumor types.